Layered Titanate H2Nd2Ti3O10 Intercalated With n-Butylamine: A New Highly Efficient Hybrid Photocatalyst for Hydrogen Production From Aqueous Solutions of Alcohols - Rodionov, Ivan A.; Maksimova, Elizaveta A.; Pozhidaev, Artem Y.; Kurnosenko, Sergey A.; Silyukov, Oleg I.; Zvereva, Irina A. (Frontiers in Chemistry, 2019)
A layered perovskite-type oxide intercalated with n-butylamine is reported as an efficient photocatalyst for hydrogen production from aqueous alcohol solution for the first time. The hybrid photocatalyst H2Nd2Ti3O10×BuNH2 was synthesized by solid-state ceramic method followed by protonation, intercalation of methylamine and subsequent substitution by n-butylamine. The product was characterized by powder XRD, TGA, STA-MS, DRS, IR and Raman spectroscopy, CHN analysis, SEM. Intercalation of n-butylamine caused a dramatic increase in photocatalytic activity of H2Nd2Ti3O10 in the reaction of hydrogen evolution from aqueous solutions of methanol, ethanol and n butanol under UV radiation. While the non-intercalated Pt-loaded H2Nd2Ti3O10 showed a maximum quantum efficiency of only 2% in the 220 – 340 nm range, the efficiency for hybrid samples reached 23% under the same conditions and after variation of experimental parameters even 52% efficiency was achieved. This effect may be associated with the significant expansion of the interlayer space, which is considered as a separate reaction zone.